Physical and Chemical Characteristics of Water in Selected Location Kiliyur Lake, Tiruchirappalli, Tamil Nadu, Southern India - Ammaiyappan, Pramila; Varadharajan, Gokula (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Lakes play a vital role in the economy of a region of a country and significant for various scholarly, societal, and economic reasons. They act as natural water reservoirs, storing large amounts of water that can be utilized for drinking, industrial processes, and irrigation, and other purposes, including hydropower generation. The quality of lake water is a critical concern for the surrounding environment and the survival of living organisms. The aim of this investigation was to explore the physico-chemical characteristics of Kiliyur Lake water. Physico-chemical parameters or factors are essential for determining water quality and identifying contaminants in specific water sources. Changes in these parameters reveal aspects of continuous change, so we must expect permanent alterations in the physical and chemical features of the lake over both spatially and temporally. As a result, describing the environment can be challenging. In our study, we divided the lake into four sites and observed the annual variations in physico-chemical parameters for the years 2022 and 2023. In the present study to examined the annual variations of physicochemical parameters such as pH, temperature, salinity, dissolved oxygen, ammonia, phosphate, nitrate, nitrite, and chloride levels. The findings from this qualitative study on the physico-chemical parameters will be invaluable for policy makers precautionary measures to protect the wetland.